The Effect of the Discovery Learning Model on Student Biology Learning Outcomes on Human Digestive System Materials Class XI SMA Negeri 2 Tondano - Etin Ruban; Helen J. Lawalata; Zusje W. M. Warouw (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This study aims to determine the influence of the Discovery Learning learning model on the cognitive learning outcomes of students' biology on the material of the human digestive system in class XI of SMA Negeri 2 Tondano. With this research method, it is quasi-experiment research. The result is a significance value (2-tailed) < 0.05, then H0 is rejected and H1 is accepted. In the results of the "t" test, a significant number (2-tailed) 0.000 < 0.05 is obtained, then H0 is rejected and H1 is accepted, meaning that there is an influence of the discovery learning model on the learning outcomes of Biology. Then it is seen from the average learning outcomes after being given treatment. Based on the results of the analysis, it shows that the average value of the experimental class at the time of the Pretest is 31.24 while the control class is 24.49. At the time of the posttest, the average score of the experimental class reached 86.82 while the control class was 57.27.